(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the artistic representation of the historical figure Mimar Sinan in Turgut Özakman’s monodrama Ben Mimar Sinan. Unlike conventional historical plays that merely glorify famous personalities, Özakman presents Sinan as both an extraordinary architect and a thoughtful human being whose achievements result from lifelong dedication, discipline, and intellectual growth. The study explores how historical facts are transformed into dramatic reality through characterization, monologue, and historical context. Particular attention is given to Sinan’s engineering achievements, artistic philosophy, and contribution to Ottoman civilization. The article argues that Özakman’s play reconstructs Mimar Sinan not only as a legendary architect but also as a cultural symbol whose ethical values and creative vision remain relevant today. Through the combination of documentary evidence and literary imagination, the playwright succeeds in creating a vivid historical character capable of inspiring contemporary audiences, especially younger generations.